Recombinant CP40 from Corynebacterium pseudotuberculosis confers protection in mice after challenge with a virulent strain. Issue 8 (17th February 2016) - Droppa-Almeida, Daniela; Vivas, Wanessa L.P.; Silva, Katharina Kelly O.; Rezende, Andrea F.S.; Simionatto, Simone; Meyer, Roberto; Lima-Verde, Isabel B.; Delagostin, Odir; Borsuk, Sibele; Padilha, Francine F.
Abstract: Background: Caseous Lymphadenitis (CLA) is a contagious, infectious, chronic disease caused by Corynebacterium pseudotuberculosis, which affects mainly sheep and goats. The clinical prevalence of CLA in Brazil is 30%, resulting in decreased milk production, weight loss, and unusable meat and leather. Prophylaxis is based on vaccination; however, current vaccinations do not offer effective protection against the infection, which makes the development of a new vaccine essential to control this disease. Experimental approach: Here, we developed a recombinant vaccine based on CP40 protein (rCP40) combined with an adjuvant (Freund's complete adjuvant or saponin) and evaluated its efficacy in a murine model of CLA. Female BALB/c mice were used in an immunization assay. Key results: rCP40 induced high levels of IgG2a and IgG2b antibodies. After challenge with a virulent strain of C. pseudotuberculosis C57 (10 4  CFU/mL), the levels of IgG2a and IgG2b were sustained, indicating a Th1 response. The groups immunized with rCP40 protein (GES and GEF groups) showed 100% protection and was statistically significant in the GES and GEF groups ( p  < 0.037 and p  < 0.0952, respectively). Conclusions: The results indicated the recombinant protein CP40 induced an specific immune response in mice that was able to afford protection after challenge, regardless the adjuvant used in the formulation.